Cat-scratch disease in young male: a case report - S., Nagamallesh C.; K., Yashashwini; M., Latha (International Surgery Journal, 2021)
Cat scratch disease (CSD) is an infectious disease caused by infected cat when it scratches a person hard enough to break the surface of skin. Although it’s a rare disease, the frequency of disease is 1 in 10,000 people. Here we are presenting a case of CSD which was diagnosed with the help of HPE and confirmed by history of scratch from patient’s pet cat. The patient was successfully treated with antibiotic therapy without any complications. However, prognosis is generally good, negligence of disease may lead to serious complications. A correlation of detailed history with clinical presentation as well as high index of suspicion will aid in accurate diagnosis of CSD.